Reflexão semântica: Termos técnicos e expressões transmitidas pela equipe de enfermagem da unidade de terapia intensiva neonatal- UTIN sobre as condições dos recém- nascido- RN e sua interferência na compreensão das mães - Sales, Rozimare Ribeiro (2015)
Starting from the assumption that expressions and technical terms transmitted by the nursing staff of the intensive care unit, interfere with the understanding of mothers of newborns; Plato "language is only an instrument of communication if participants use words in the same sense, it is a necessary mediation that enables communication and facilitates human knowledge. Philosophers and linguists for the language should not be used randomly, the speaker can not be used certain terms or expressions freely. Linguistics is a science that investigates the human verbal language. In this study, we used the scientific knowledge of Semantic Linguistics, which provides scientific explanations of the phenomena of linguistic meaning, considering that the nursing staff to develop activities with mothers, uses as a tool expressions and technical terms, with no concern to find out if they know the words present in dialogue. Goals: Verify the existence of technical terms or expressions that hinder the understanding of mothers; verify that the mothers of newborn intensive care unit understand the technical terms or expressions passed by the nursing team; list the technical terms used by the nursing team; Display a list of meanings of expressions and technical terms used by the nursing team, when they communicate with mothers about the newly nascido.Metodologia: descriptive, exploratory study with qualitative literature review, the study population were mothers of intensive care unit , newborn for data collection was used a questionnaire. Conclusion: The study demonstrated the contribution of semantics Linguistics for nursing proving that the newborn intensive care unit nursing staff must change your language content used in communication with their mothers because the expressions and technical terms used routinely hinders the understanding of mothers, since, if the receiver does not understand the meaning that the speaker expresses, the transmission will not be understood, not reaching the proposed goal is the empowerment of mothers efficiently to care for their newborns in the post-discharge.